Experimental study of the effects of siestas on the nocturnal sleep quality and thermal comfort levels under thermoneutral environment in summer - Huili Yu; Xue Zhao; Liping Chen; Xiaohui Tian; Shimin Liang; Songtao Hu (Energy and Built Environment)
It has been determined that siestas could potentially have both mental and physical influences on the human body. However, the effects of siestas on the nocturnal sleep quality and thermal comfort levels under thermoneutral environment had not yet been examined in detail. In order to explore the potential influences of siestas on nocturnal sleep, twenty subjects were recruited and divided into two groups based on whether they took siestas or not. During this study's experiment, the temperature was maintained at 25 °C, and sleep duration was recorded throughout the night. In addition, thermal comfort votes (TCV) and thermal satisfaction votes (TSV) were obtained both before and after the nocturnal sleep. Furthermore, dopamine (DA) levels, which played important roles in emotional regulation, were measured after the nocturnal sleep. Results showed that the siesta group had a significant increase in self-reported nocturnal sleep quality (p < 0.05), although slight decreases in slow-wave sleep (SWS) duration and rapid eye movement (REM) duration were observed. Additionally, higher TCV and TSV values were reported in the siesta group (p < 0.05). Higher DA concentration was also detected in the siesta group after the nocturnal sleep. Furthermore, some correlations were illustrated between the thermal voting values and the sleep duration, as well as the DA concentration levels. Results implied that siestas could have an influence on the nocturnal sleep quality and thermal comfort levels under thermoneutral environment. Besides, DA concentration levels played an important role in the thermal comfort evaluations when exploring the influences of siestas on nocturnal sleep.